1998
DOI: 10.1034/j.1600-0420.1998.760205.x
|View full text |Cite
|
Sign up to set email alerts
|

Corneal epithelium and UV‐protection of the eye

Abstract: ABSTRACT.Purpose: To study UV-absorption and UV-induced fluorescence in the bovine corneal epithelium. Methods: Spectrophotometry and spectrofluorimetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 17 publications
1
58
0
2
Order By: Relevance
“…The fluorescence calculated as arbitrary units per milligram of protein is higher in the corneal tissue than in SIRC. Indeed it is likely that the release of other fluorescent substances produced by the ROS-generating system on articulate arrangement of corneas can justify this increase [8,51,52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescence calculated as arbitrary units per milligram of protein is higher in the corneal tissue than in SIRC. Indeed it is likely that the release of other fluorescent substances produced by the ROS-generating system on articulate arrangement of corneas can justify this increase [8,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the effect of UV light has been extensively investigated [1][2][3][4][5][6][7][8]. It has been reported that biotoxic epiphenomena may take place when the threshold level of radiation absorbed in corneal tissues is exceeded, and, consequently, permanent keratocyte damage or loss, epithelium destruction, endothelium edema and necrosis occur, as well as biochemical changes, such as ROS production, protein cross-linking, enzyme inactivation, DNA strand breaks and chemotactic factor release [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…There is recent biophysical evidence showing that UV light penetrates and is differentially absorbed by ocular tissues. Their absorption pattern in the antero-posterior direction follows a wavelength-dependent decade (Ringvold and Davanger, 1985;Ringvold, 1997Ringvold, ,1998. The corneal epithelium absorbs UV wavelengths shorter than 310 nm (UV-B between 290 and 320 nm and UV-C between 200 and 290 nm) thereby acting as a filter and protecting the lens and retina from UV-induced damage (Fig.…”
Section: Uv Irradiation-induced Cellular Damagementioning
confidence: 99%
“…6). In doing so the corneal epithelium and lens protect the retina from UV irradiation-induced damage (Ringvold, 1998;Taylor et al, 1998;Podskochy et al, 2000). In addition, repeated subthreshold or single threshold UV-exposures lead to inhibition of mitosis, nuclear fragmentation and loss of the whole corneal epithelial layer.…”
Section: Uv Irradiation-induced Cellular Damagementioning
confidence: 99%
“…These include antioxidants, lens chromophores, melanin, glutathione (GSH) peroxidase, superoxide dismutase, and heme oxygenase [106]. Radical scavengers such as vitamin E, vitamin C, [107,108] beta carotene, and ubiquinone [107] are other defense mechanisms.…”
Section: Ocular Photoprotectionmentioning
confidence: 99%